BÖBREĞİN HİDATİK KİST HASTALIĞI - ÖZKAN, Burak; SANCAKLI, Özgür; ÇİTÇİ, Şefik and DEMİRKESEN, Oktay and ALICI, Bülent (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Cystic hydatic disease is a parasitic infestation caused by the larval form of Echinococcus granulosus. It is endemic in parts of Africa, Latin America, Mediterranean and Turkey. Hydatic cysts are mostly evident in the liver and lungs, while renal involvement is rare, comprising only 2% to 4% of cases. Renal hydatid disease mimicked other diseases. The combination of clinical history, imaging studies and serological, urine investigation yielded a reliable pretreatment diagnosis in only 50 % of cases and a presumptive diagnosis in 71%. Among imaging studies computerized tomography was the most valuable diagnostic examination. Moderate eosinophilia was found in half of the cases while a third of cases had scoleces in the urine. Renal sparing approach should be intended when preoperative diagnosis of hydatidosis has been considered. Renal conservative surgery is possible even for large lesions. Cystectomy is the simplest technique and can be followed safely by pedicled omentoplasty to treat residuel cavity. Nephrectomy is also electively performed for large lesions when the cyst causes tissue damage by pressure atrophy and in cases with evident communication with the urinary tract. The risk of surgical spillage and severe allergic reaction to the cyst should be considered. AIso, a renal preserving strategy may fail. However, medical management of disease is far from being a realistic option to surgery and should be conceived as adjuvant therapy or an alternative for poor surgical candidates.